Suicide in Patients with Motor Neuron Disease - S. Bak; E. N. Stenager; E. Stenager; J. Boldsen; T. A. Smith (Behavioural Neurology)
The aim of the present study was to assess, through an epidemiological study, whether suicide risk is increased in patients with motor neuron disease (MND). The study involved 116 patients with MND. In the study period 92 patients died, 47 males and 45 females. No patients committed suicide. The number of expected suicides was 0.27 for males and 0.12 for females, a total of 0.38. The difference between observed and expected suicides was not statistically significant for males and females.